Results of the application of the Protocol for Improved Recovery in Surgery (PREMEC) in the surgical treatment of colorectal cancer at the Edgardo Rebagliati National Hospital – EsSalud - Ortega Checa, David (2020)
Introduction: Improvement in health care is reflected in achieving better results in quality indicators. For quite some time several programs have pursued a reduction of complications and length of stay. A program called Protocol for Improved Recovery in Surgery (PREMEC) has been implemeted at the colorectal surgery service. Objective: The objective of this study is to show results of the implementation of PREMEC. Materials and methods: This is an observational study of two cohorts, 516patients were included. One is a historic cohort (before the protocol) comprised by patients who underwent resective colonic and rectal surgery through an open approach from January 2017 to November 2018. The other prospective cohort includes patients treated under the PREMEC program from December 2018 through to March 2020. This cohort was divided into two groups according to the surgical approach, open and laparoscopic. All groups were compared regarding postoperative length of stay, complications, mortality and readmissions. Results: Groups were similar in age, sex, cancer staging and type of surgery. Length of stay was 13.86 days (SD 7.86 days) for the pre-PREMEC group, 10.62 days (SD 5.4 days) for the PREMEC open groupand 6.86 days (SD 2.7 days) for the PREMEC laparoscopic group. As for complications the PREMEC group showed a decrease in anastomotic leaks, Surgical Site Infection (SSI) and postoperative ileus. No differences were found regarding mortality, reoperations and readmissions. Conclusion: Implementation of the PREMEC program attained a decrease in length of stay, anastomotic leaks, SSI and postoperative ileus with no increase in mortality, reoperations or readmissions.